(untitled) (Journal of the College of Basic Education, 2022)
Studying began with the widespread of the informntris and the covid 19 pandemic , which causes new ways to adapt to the current health crisis and quarantining . from here we starts using the word wide web or internet to teach. Not only in Iraq but all around the world. The first semester of using it was clouded with questions like : 1- Can the teacher up bring ager arution academically. 2- Can the teacher with stand all the difficulties that come with teaching. 3- Can the teacher improve his / her technical shills . And there was a great importer on both the teaching staff and the students .the goal was to identify : the Reba bilitation of the teaching staff by means of virtual classed between the teacher and students . The second semester was demes by three thesis : 1-the education dimension of e-learning . 2- the teacher and virtual learning. 3- platform e-learning. The third semester was high lights with the disabilities of the virtual learning system . Also the features of e-learning was highlighted . It is summers up to: 1- Although e-learning was met by difficulties we can bypass that through mahing a better place to teach. 2- we can spreard the electronic culture using the different platforms. 3- it is necessary to open educational courses for teachers to improve three electronical skills and finally the study concluded with recommendation from English sources.